Trends and correlated outcomes in population-level prescription opioid and transdermal fentanyl use in Israel - Barak Shapira; Ronny Berkovitz; Ziona Haklai; Nehama Goldberger; Irena Lipshitz; Paola Rosca (BMC, 2023)
Abstract Background In the last twenty years, there was a documented increase in prescription opioid procurement in Israel. However, there is still little evidence of the association between opioid procurement rates, health service utilisation in secondary care, and enrollment rates to substance use disorder treatment programmes. In this study, we show trends in the reports of opioid-related hospitalisations, emergency department visits, enrollment to community-based outpatient treatment for Prescription Opioid Use Disorder and opioid-related mortality rates. Additionally, we examine potential correlations between these health service utilisation rates and prescription opioid procurement rates at the population level, with a focus on transdermal fentanyl. Methods A longitudinal study at the population level. We used seven-year data on indicators of opioid-related morbidity, prescription opioid procurement data for 2015-2021, and six-year opioid-related mortality data for 2015-2020. We measure the correlation between procurement rates of prescription opioids in Oral Morphine Equivalent per capita, and aggregated rates obtained from hospital administrative data for hospitalisations, emergency department visits, and patient enrolment in specialised prescription opioid use disorder outpatient treatment in the community setting. Results Between 2015 and 2021, procurement rates in primary care per capita for all prescription opioids increased by 85%, while rates of transdermal fentanyl procurement increased by 162%. We found a significant positive correlation at the population level, between annual opioid procurement rates, and rates per population of opioid-related visits to emergency departments (r = 0.96, p value < 0.01, [CI 0.74-0.99]), as well as a positive correlation with the rates per population of patient enrolment in specialised prescription opioid use disorder outpatient treatment (r = 0.93, p value = 0.02, [CI 0.58-0.99]). Opioid-related mortality peaked in 2019 at 0.31 deaths per 100,000 but decreased to 0.20 deaths per 100,000 in 2020. Conclusion Data shows that all-opioid and transdermal fentanyl procurement has increased yearly between 2015 and 2021. This increase is positively correlated with a growing demand for community-based Prescription Opioid Use Disorder outpatient treatment. Efforts to reduce opioid-related morbidity may require effective approaches toward appropriate prescribing, monitoring, and further increasing access to prescription opioid outpatient treatment.